2019
DOI: 10.3390/app9020332
|View full text |Cite
|
Sign up to set email alerts
|

Damage Analyses of Replaceable Links in Eccentrically Braced Frame (EBF) Subject to Cyclic Loading

Abstract: In the current design of steel eccentrically braced frames (EBFs), the yielding link is coupled with the floor beam. This causes the design of cross-sectional dimensions of links to be enlarged, resulting in over-designed structures and foundations, and increasing the cost of the overall structure. In addition, the beams are forecast to sustain severe damage through repeated inelastic deformations under design-level earthquakes, and thus the structure may require extensive repair or need to be replaced. To imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
0
9
0
3
Order By: Relevance
“…According to studies by Yin et al on the replaceable links in eccentrically braced frame subject to cyclic loading, it was observed that the links in this shear device had inelastic deformation concentrated in the link showing extremely stable hysteresis behavior, and damaged links were replaced easily as end-plate connections were adopted. This paper proposes a piezoceramic patch transducer-based active sensing approach to monitor the crack onset and development of the EBF when subjected to dynamic loadings [23]. Numerous studies have been carried out regarding the effects of SSI on different structures and calculating their damage index.…”
Section: Introductionmentioning
confidence: 99%
“…According to studies by Yin et al on the replaceable links in eccentrically braced frame subject to cyclic loading, it was observed that the links in this shear device had inelastic deformation concentrated in the link showing extremely stable hysteresis behavior, and damaged links were replaced easily as end-plate connections were adopted. This paper proposes a piezoceramic patch transducer-based active sensing approach to monitor the crack onset and development of the EBF when subjected to dynamic loadings [23]. Numerous studies have been carried out regarding the effects of SSI on different structures and calculating their damage index.…”
Section: Introductionmentioning
confidence: 99%
“…The work [19] analyzed the change of stress (measured by strain gauges) in bolts, depending on the change in the bolt head surface (the head was cut off to simulate a corrosion defect). Stress concentration issues, especially around welds of connections subjected to cyclic loading (e.g., seismic), were analyzed in [20].…”
Section: Introductionmentioning
confidence: 99%
“…The validity of this method has been verified by eight near-full-size EBF tests under quasi-static cyclic loading. In addition, Stephens and Yin [39,43] recommended a bolted end plate connection detail for replaceable links that utilized fillet welds at the link-to-endplate interface recently.…”
Section: Introductionmentioning
confidence: 99%
“…In past researches, there were many on the end plate connection type energy dissipation beam, but few on the web connection type. Based on the previous researches [42][43][44][45], it can be found that the failure of the end plate connection type energy dissipation link is mainly due to the failure of the flange and the failure of the weld, which reduces the constraint of the flange on the web and further leads to the reduction of the bearing capacity of the link. This paper presents an experimental research program that utilizes web connections at the link-to-beam interface.…”
Section: Introductionmentioning
confidence: 99%